MRI morphologic alterations after liver SBRT - Boda-Heggemann, Judit; Attenberger, Ulrike; Budjan, Johannes; Jahnke, Anika; Vogel, Lena; Simeonova-Chergou, Anna; Herskind, Carsten; Wenz, Frederik; Lohr, Frank (Strahlentherapie und Onkologie, 2016)
AimCT morphologic and histopathologic alterations have been reported after SBRT. We analyzed the correlation of MRI morphologic alterations with radiation doses to assess the potential for MRI-based dose-effect correlation in healthy liver tissue.Patients and methodsMRI data of 24 patients with liver metastases 7±3 weeks after image-guided SBRT in deep-inspiration breath-hold were retrospectively analyzed. MRI images were intermodally matched to the planning CT and corresponding dose distribution. Absolute doses were converted to EQD2,α/β =x with α/β values of 2, 3 for healthy liver tissue, 8 Gy for modelled predamaged liver tissue and 10 Gy for tumor tissue.ResultsA central nonenhancing area was observed within the isodose lines of nominally 48.2 ± 15.2 Gy, EQD2Gy/α/β =10 92.5 ± 27.7 Gy. Contrast-enhancement around the central nonenhancing area was observed within the isodose lines of nominally 46.9 ± 15.3 Gy, EQD2Gy/α/β =10 90.5 ± 28.3 Gy. Outside the high-dose volume, in the beam path, characteristic sharply defined, nonblurred MRI morphologic alterations were observed that corresponded with the following isodose lines: T1-intensity changes occurred at isodose lines of nominally 21.9 ± 6.7 Gy (EQD2,α/β =2 42.5 ± 8.7 Gy, EQD2,α/β =3 38.5 ± 7.6 Gy, EQD2,α/β =8 30.2 ±6.3 Gy). T2-hyper/hypointensity was observed within isodose lines of nominally 22.4 ± 6.6 Gy (EQD2,α/β=2 42.7 ± 8.1 Gy, EQD2,α/β=3 38.7 ± 7 Gy; EQD2,α/β=8 30.5 ± 5.9 Gy).ConclusionsUsing deformable matching, direct spatial/dosimetric correlation of SBRT-induced changes in liver tissue was possible. In the PTV high-dose region, a central nonenhancing area and peripheral contrast medium accumulation was observed. Beam path doses of 38-42 Gy (EQD2,α/β =2-3) induce characteristic MRI morphologic alterations.
Gesehen am 31.07.2019